Burnout Among EFL Teachers in Indonesia: Levels and Factors - Utami, A. A. Istri Dewi Adhi; Sidaryanti, Ni Nyoman Asri; Wirahyuni, Kadek (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
Having highly motivated teachers is vital for effective teaching in foreign language classroom. Nevertheless, burnout may impair teachers' performance and negatively impact how they engage with students. The current study aimed at investigating the level of burnout among EFL teachers in Indonesia. This study was a mixed method study followed by forty-five EFL teachers who are currently teaching in high school level. Using Maslach Burnout Inventory Educators Survey, it was found 57.8% of participants responded they felt high levels of emotional exhaustion, followed by moderate levels (31.1%) and high levels (11.1%). Comparably, approximately 17.8% of the teachers felt they were not depersonalized, compared to 37.8% who felt it was moderate and 44.4% who felt it was extreme. High level of burnout was experienced by teachers with less than five years of teaching experience. Low to moderate level of burnout was found in teachers with more than five years experiences. Regression analysis found that length of experience significantly influences EFL teachers’ level of burnout (Sig. <.05). A further interview confirmed the factor that caused burnout among teachers such as teaching administration, adapting with technology, and dealing with misbehave students. This study highlighted the importance of addressing teachers’ burnout level.